Procedural justice perceptions, legitimacy beliefs, and compliance with the law: a meta-analysis - Walters, Glenn D. (Journal of experimental criminology, 2019)
The purpose of this study was to compare procedural justice and legitimacy as correlates and predictors of compliance with the law.